YOLO Juliet - Shakespeare, William; Wright, Brett (2015)
A modernized adaptation of William Shakespeare's play about the star-crossed lovers Romeo and Juliet, told through texts, complete with emojis and hashtags.
Keywords: Shakespeare, William, -- 1564-1616. -- Adaptations